State Bank of India vs Unit Trust of India: A Comparison of Performance of Mutual Fund Schemes - Mehta, Sushil Kumar (Indian Journal of Finance, 2010)
The changing financial services scenario emerging by virtue of liberalization in last one decade has introduced a vast variety of concepts. Mutual fund is one of these. Mutual funds in Indian context are a recent phenomenon. In a short span of less than one decade, it has changed the investment pattern of medium and small Investors in India. The origin of the Indian mutual fund industry can be traced back to 1964 when the Indian government, with a view to augment small savings within the country and to channelise these savings to the capital markets, set up the Unit Trust of India (â€œUTIâ€). The UTI was setup under a specific statute, the Unit Trust of India Act, 1963. The Unit Trust of India launched its first open-ended equity scheme called US 64 in the year 1964, which turned out to be one of the most popular mutual fund schemes in the country. In 1987, the government permitted other public sector banks and insurance companies to promote mutual fund schemes. Pursuant to this relaxation, six public sector banks and two insurance companies viz. Life Insurance Corporation of India and General Insurance Corporation of India launched mutual fund schemes in the country. Subsequently, in 1993, the Securities and Exchange Board of India ("SEBI") introduced The Securities and Exchange Board of India (Mutual Funds) Regulations, 1993, which paved way for the entry of private sector players in the mutual fund industry.